Design and Optimization of Hydrodynamically Balanced Oral In situ Gel of Glipizide - G. Swathi, P. K. Lakshmi (Journal of Applied Pharmaceutical Science, 2015)
Objective: The purpose of the present investigation was to formulate hydrodynamically balanced oral In situ gel of glipizide inorder to increase the gastric residence time and to modulate the release behavior of the drug. Material and method: In situgel formulations were prepared by using different concentrations of sodium alginate, calcium carbonate, trisodium citrate and release retardant polymers. pH triggered ionic gelation is the mechanism involved in the present study. Taguchi L9 OA experimental design was employed for the optimization of formulations. All the formulations were subjected to various evaluation parameters. Results: Formulation F9 containing 3% of sodium alginate, 1.0 % of CaCO3, 0.2% of trisodium citrate and 0.5% of HPMC-K100M was selected as optimized batch based on Q12 58.26%, floating time 47.76 sec and drug content 98.2%. The release pattern of drug was found to follow first order. The value of ‘n’ from Korsemeyer equation was found to be 1.00 indicating the drug release by supercase II. The DSC study revealed that there was no incompatibility. Gastroretentive X-ray imaging study on Albino rabbit demonstrated that it was able to float in the stomach for more than 8hrs. Pharmacodynamic study on Wistar rats demonstrated significant hypoglycaemic activity of the optimized formulation. Conclusion: It was concluded that the hydrodynamically balanced oral In situ gel of glipizide could be an effective dosage form which remains buoyant and sustain the drug release for 24hrs.
Keywords: Hydrodynamically balanced, In situ gel, sodium alginate, gastroretentive.